Die Nutzung von Evaluationen in den Schweizer Parlamenten - Eberli, Daniela (Seismo, 2019)
Evaluations assess the effectiveness of a public policy using a scientific approach and thus provide bases to make effects-oriented and well-founded decisions in parliament. Although policy evaluations have been established in Switzerland, research on their role in the parliaments is limited. This book investigates the use of policy evaluations and its explaining factors based on a survey of cantonal and national members of parliament and studies of cantonal legislative processes. In doing so, it contributes to the question of what role knowledge plays in today's modern parliaments.